JURNI (Journeying with Patients' Understanding and Responding to Needs Interactively): An In-Hospital Navigation Application for Timely Diagnosis and Treatment of Breast Cancer at the University Malaya Medical Centre. - Dhillon, Sarinder Kaur; Kalhor, Foad; Seng Kai, Wong; Mei Sze, Teh; Mohd Shariff, Nisha; Sekaran, Manisha; Taib, Nur Aishah (Health Services Insights, 2024)
One of the main challenges in breast cancer management is health system literacy to provide optimal and timely diagnosis and treatments within complex and multidisciplinary health system environments. Digitalised patient navigation programs have been developed and found to be helpful in high- and low-resource settings, but gaps remain in finding cost-effective navigation in the public sector in Malaysia, where resources are scarce and unstable. Hence, we set out to develop a virtual patient navigation application for breast cancer patients to enhance knowledge about cancer diagnosis and treatments and provide a tracking mechanism to ensure quality care. This paper identifies the requirement for in-hospital patients' navigational needs for cancer diagnosis, the cancer diagnosis and treatment process's components and pathways, developing the app and usability study on the usefulness of a cancer navigation mobile application in navigating cancer care at the University of Malaya Medical Centre (UMMC). Key features found when designing the in-hospital application are managing the medical appointments, finding the location of each medical department, and providing information to breast cancer patients, healthcare managers and providers to ensure a coordinated care pathway. In future work, we plan to implement the JURNI in-hospital patient navigation and perform usability studies involving the actual patients, physicians and administrators. We are also working towards enhancing data security, adding other local languages and artificial intelligence capabilities to improve the patient's journey.